Crush the king - Estep, Jennifer (Estep, Jennifer. Crown of shards novel., 2020)
"Queen Everleigh Blair of Bellona has survived the mass murder of the royal family, become a fearsome warrior trained by an elite gladiator troupe, and unleashed her ability to destroy magic. After surviving yet another assassination attempt orchestrated by the conniving king of Morta, Evie has had enough. It's time to turn the tables and take the fight to her enemies. There is no better opportunity to strike than during the Regalia Games, a time when warriors, nobles, and royals from all the kingdoms come together to compete in various sporting events. With the help of her loyal friends, Evie goes on the attack at the Regalia, but things don't turn out the way she hopes. Soon, she is facing a terrifying new threat, and she will have to dig deep and learn even more about her growing magic if she has any chance of defeating her foes. Because to secure her throne and ensure her kingdom's survival, Evie must think like a true Bellonan: she must outsmart and outwit her enemies . . . and crush the king."--Page [4] of cover.